Legal Protection of Hospitals as Whistleblowers According to the Republic of Indonesia Act Number 17 of 2023 Concerning Health in Cases Involving Fake Doctors - Aditya Pratama Sarwono (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
This research explores legal protection for hospitals as whistleblowers in doctor identity forgery cases, emphasizing the Act of the Republic of Indonesia Number 17 of 2023 on Health in Indonesia. These cases, as seen in Primasatya Husada Citra Hospital (PHC) Surabaya, revealed vulnerabilities in the healthcare system to individuals without proper qualifications, highlighting the potential criminal penalties for hospital directors due to negligence in recruiting fake doctors. This research aims to delve into the Health Law's content and find strategies to help hospitals minimize criminal liability risks and ensure compliance with this law. The focus of the analysis will be on key legal aspects affecting the legal protection of hospitals in reporting cases of doctor identity forgery. The results will provide valuable guidance to hospitals in maintaining the integrity of healthcare services, protecting hospitals, and ensuring the safety of patients from the challenges of doctor identity forgery by irresponsible individuals.